Assessment Of Complex Ii Fuel Oil Heat Exchanger Utilizing Heat Transfer Methodology - Sulistiyo Nugroho, Budi; Ivonne Aqilah, Griselda; Alvino, Nimrod (International Journal of Science, Technology & Management, 2024)
The heating stage of oil and gas refining commences with a heat exchanger. Using the pressure drop method and dirt factor in conjunction with the utmost standard permissible limit is one method of evaluating the thermal efficiency of a heat exchanger. This is performed to ascertain the value of the pressure drop, or pressure drop, which is directed at the fluid passage in the shell and pipeline. Moreover, a dust factor value is necessary to account for the potential accumulation of impurities and scale on the walls outside the heat exchanger conduit. The dust factor value is the maximum value that the parameter permits to ascertain the feasibility of the heat exchanger. Heat Exchanger 011-E-112 in the Fuel Oil Complex Unit The results indicate that heat exchanger 11E-112 can still be utilized despite the necessity for design enhancements. The design data for the shell is 1.7 psi, and the tube is approximately 18.92 psi. The Dirt Factor values for the shell and tube are 0.017 BTU/hour ft2°F and 0.034 BTU/hour ft2°F, respectively. The tube pressure drop value is 130.32 psi, while the shell pressure drop value is 2.53 psi.